Side effects and tolerability of combination blood pressure lowering according to blood pressure levels: an analysis of the PROGRESS and ADVANCE trials. Issue 6 (June 2017) - Atkins, Emily R.; Hirakawa, Yoichiro; Salam, Abdul; Woodward, Mark; Cooper, Mark; Hamet, Pavel; Harrap, Stephen; Lees, Kennedy; Liu, Lisheng; Mancia, Giuseppe; Marre, Michel; Perkovic, Vlado; et al.
Abstract : Objective: To measure the placebo-controlled effects of combination therapy on hypotension, treatment discontinuation, and major renal outcomes, according to baseline blood pressure. Methods: We conducted an analysis of the action in diabetes and vascular disease: preterax and diamicron-MR controlled evaluation ADVANCE and perindopril protection against recurrent stroke study PROGRESS trials, including 14 684 participants allocated combination therapy or placebo. The mean age was 65 years, 61% were men, and 64% were receiving background blood pressure lowering (BPL) therapy. Participants were stratified into five subgroups by baseline SBP less than 120, 120–129, 130–139, 140–159, and at least 160 mmHg. Discontinuation of study treatment during the active run-in phase and postrandomization follow-up was assessed for hypotension/dizziness and other causes. Major renal outcomes (sustained doubling in creatinine or renal death) were also assessed. Results: Discontinuation during the 4–6-week active run-in phase due to hypotension/dizziness ranged from 3.6% in those with SBP less than 120 mmHg to 1.3% in those with SBP at least 160 mmHg. Median follow-up in the randomized phase was 5.6 years, and discontinuation for hypotension was higher with combination therapy compared with placebo in the less than 120 mmHg group (4.7 vs. 1.2%). However, for each subgroup with baseline SBP 120–129, 130–139, and 140–159 mmHg, the absolute excess of discontinuation due to hypotension with combination therapy was 0.7%. Total discontinuations were only increased in the less than 120 mmHg group (18.4 vs. 12.5%) and the 120–129-mmHg subgroup (17.6 vs. 14.2%). There were no clear differences across the SBP subgroups for the combined renal outcome (overall, 0.8 vs. 0.6%). Conclusion: Compared with those with baseline SBP 140–159 mmHg, side effects of dual combination BPL are essentially the same for people with SBP 130–139 mmHg and only modestly increased among patients with SBP 120–129 mmHg. During long-term therapy, side effects sufficient to stop treatment that are treatment related (i.e. occur in excess of rates seen with placebo) occur at less than 0.5%/year in patients with baseline SBP 120–139 mmHg. These results have important implications in assessing the likely balance of benefits and side effects of BPL with combination therapy among those with SBP 120–139 mmHg. Abstract : Supplemental Digital Content is available in the text